2001
DOI: 10.1183/09031936.01.00090001
|View full text |Cite
|
Sign up to set email alerts
|

Initial risk class and length of hospital stay in community-acquired pneumonia

Abstract: Initial risk class and length of hospital stay in community-acquired pneumonia. R. Menéndez, D. Ferrando, J.M. Vallés, E. Martínez, M. Perpiñá. #ERS Journals Ltd 2001. ABSTRACT: The total medical costs of community-acquired pneumonia are directly related to the costs of hospital admission and length of stay. The aim of the present study was to evaluate the reasons for prolonged duration of stay in patients stratified in five risk classes for death, and to identify factors associated with prolonged stay.The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
2
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 27 publications
6
40
2
4
Order By: Relevance
“…Due to the retrospective study design of this survey, it may be that the lack of careful recording into the charts has caused an overestimation of unnecessary days of hospitalisation. However, our finding is unique: In a prospective survey where the physicians responsible for discharge were aware of the study, Menendez et al [30] reported that the overall percentage of patients with inappropriate length of hospital stay was 68%. In another prospective study, Halm et al [9] showed that 65-86% of 686 patients with CAP stayed in hospital for at least a 1 day after having reached stability.…”
Section: Discussionmentioning
confidence: 61%
“…Due to the retrospective study design of this survey, it may be that the lack of careful recording into the charts has caused an overestimation of unnecessary days of hospitalisation. However, our finding is unique: In a prospective survey where the physicians responsible for discharge were aware of the study, Menendez et al [30] reported that the overall percentage of patients with inappropriate length of hospital stay was 68%. In another prospective study, Halm et al [9] showed that 65-86% of 686 patients with CAP stayed in hospital for at least a 1 day after having reached stability.…”
Section: Discussionmentioning
confidence: 61%
“…The current study, like others [16][17][18][19][20], shows the suitability of the risk factors for death of the PSI-scoring system in the present authors9 local setting. Other authors have shown that pre-defined PSI scores have a good discriminant capacity but risk of death is overestimated [21].…”
Section: Discussionmentioning
confidence: 95%
“…Tras analizar los criterios de ingresos de los pacientes afectos de NAC en nuestra serie, sólo cinco de ellos se consideraron como innecesarios; la tasa de reingresos (2,7%) ha sido más baja que las descritas (3,4%) (12).…”
Section: Discussionunclassified